(untitled) (Proceedings of International Educators Conference, 2023)
In the opinion of Foreign Language Learners, Gardner states that “when an individual has a desire to learn a foreign language, and this is a sign that a person is ingrained in learning a foreign language”. Oxford edit dictionaries define motivation as follows. ”Defined as the action or manifestation of a person in his or her actions". Motivation is considered an abstract concept, and determining motivation is a challenge. Through motivation, students studying a foreign language stand out, as it is evident that they have a high passion for learning a foreign language and that they achieve a better result in mastering a foreign language. Motivation plays an important role for foreign language learners. Educators who teach Agar relate motivation to language learning